Combined ART started during acute HIV infection protects central memory CD4+ T cells and can induce remission. (21st April 2015) - Chéret, Antoine; Bacchus-Souffan, Charline; Avettand-Fenoël, Veronique; Mélard, Adeline; Nembot, Georges; Blanc, Catherine; Samri, Assia; Sáez-Cirión, Asier; Hocqueloux, Laurent; Lascoux-Combe, Caroline; Allavena, Clotilde; Goujard, Cécile; et al.
Abstract: Background: Therapeutic control of HIV replication reduces the size of the viral reservoir, particularly among central memory CD4+ T cells, and this effect might be accentuated by early treatment. Methods: We examined the effect of ART initiated at the time of the primary HIV infection (early ART), lasting 2 and 6 years in 11 and 10 patients, respectively, on the HIV reservoir in peripheral resting CD4+ T cells, sorted into naive (TN), central memory (TCM), transitional memory (TTM) and effector memory (TEM) cells, by comparison with 11 post-treatment controllers (PTCs). Results: Between baseline and 2 years, CD4+ T cell subset numbers increased markedly ( P  < 0.004) and HIV DNA levels decreased in all subsets ( P  < 0.009). TTM cells represented the majority of reservoir cells at both timepoints, T cell activation status normalized and viral diversity remained stable over time. The HIV reservoir was smaller after 6 years of early ART than after 2 years ( P  < 0.019), and did not differ between PTCs and patients treated for 6 years. One patient, who had low reservoir levels in all T cell subsets after 2 years of treatment similar to the levels in PTCs, spontaneously controlled viral replication during 18 months off treatment. Conclusions: Early prolonged ART thus limits the size of the HIV reservoir, protects long-lived cells from persistent infection and may enhance post-treatment control.